'Start smart': using front-line ownership to improve the quality of empiric antibiotic prescribing in a paediatric hospital. Issue 3 (19th August 2019) - Cunney, Robert; Kirrane-Scott, Michelle; Rafferty, Aisling; Stapleton, Patrick; Okafor, Ikechukwu; McNamara, Roisin
Abstract : Infection is the most frequent indication for non-scheduled admission to paediatric hospitals, leading to high levels of empiric antibiotic prescribing. Antibiotic prescribing in line with local guidelines, improves patient outcomes, reduces adverse drug events and helps to reduce the emergence of antimicrobial resistance. We undertook an improvement project at Temple Street Children's University Hospital targeting documentation of indication and compliance with empiric antibiotic prescribing guidelines among medical admissions via the emergency department (ED). Results of weekly audits of empiric antibiotic prescribing were fed back to prescribers. Front-line ownership techniques were used to empower prescribers to generate ideas for change, such as regular discussion of antibiotic prescribing issues at weekly clinical meetings, antibiotic 'spot quiz', updates to prescribing guidelines, improved access and promotion of a prescribing app, laminated guideline summary cards, and reminders and guideline summaries at a point of prescribing in ED. Documentation of indication and guideline compliance increased from a median of 30% in December 2014 to 100% in March 2015, and was sustained at 100% to September 2016, then 90% to December 2017. The intervention was associated with improvements in non-targeted indicators of prescribing quality, an overall reduction in antimicrobial consumption in the hospital, and a €105 000 reduction in annual antimicrobial acquisition costs. We found that a simple, paper-based, data collection system was effective, provided opportunities for a point-of-care interaction with prescribers, and facilitated weekly data feedback. We also found that using a pre-existing weekly clinical meeting to foster prescriber ownership of the data, allowing prescribers to identify possible tests of change, and exploiting the competitive nature of doctors, led to a rapid and sustained improvement in prescribing quality. Awareness of local prescribing processes and culture are essential to delivering improvements in antimicrobial stewardship.